Procedings of the British Machine Vision Conference 1993 1993
DOI: 10.5244/c.7.56
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Model-Based Traffic Vision

Abstract: Model based vision allows use of prior knowledge of the shape and appearance of specific objects to be used in the interpretation of a visual scene; it provides a powerful and natural way to enforce the view consistency constraint [I]. A model based vision system has been developed within ESPRIT VIEWS: P2152 which is able to classify and track moving objects (cars and other vehicles) in complex, cluttered traffic scenes. The fundamental basis of the method has been previously reported [2]. This paper presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It operates by evaluating evidence for straight lines in one or more images of an object [20]. A line can be an edge (first difference) or bar (second difference) in an image.…”
Section: Facet Modellermentioning
confidence: 99%
“…It operates by evaluating evidence for straight lines in one or more images of an object [20]. A line can be an edge (first difference) or bar (second difference) in an image.…”
Section: Facet Modellermentioning
confidence: 99%
“…We report experiments to demonstrate the performance of the modified algorithms. The output of the algorithms provides initial pose and class estimates which can be used to bootstrap model-based pose refinement (e.g., [35]) and vehicle tracking (see [6], [22], and [23]] for examples of tracking systems).…”
Section: Introductionmentioning
confidence: 99%
“…The open world scene however can be a complex image to analyse, particularly due to illumination variations within the image and the changing pose of the object, each of which complicate the frame to frame matching of objects moving within the scene. Feature based geometric model matching, [2,4,10] has been shown to be very successful for identifying and tracking objects moving within a open world image, where the objects to be tracked occupy a significant proportion of the image; however they are less successful when the object to be tracked is further away from the camera and hence only occupying a small proportion of the image. In this case it has been found that the matching of crude object descriptors is more robust, [1,3].…”
Section: Introductionmentioning
confidence: 99%